Is the heart home?Features of the methaphoricalheartimage in medical discourse - Russkaia T. N., Khakhalova S. A. (Current trends in the development of education system, 2020)
this article considers methaphorical models that represent the heart as a part of human body in the minds of native Russian speakers.Their frames and slots have been identified.The axiological parameter of presented metaphors is interpreted.
Keywords: фрейм; frame; концептуальная метафора; слот; world image; conceptual methaphor; methaphorical modelling; slot; mental space; blend; образ мира; метафорическое моделирование; ментальное пространство; бленд